FEATURES OF FORMING SPORTS AND LEISURE COMPLEXES IN THE STRUCTURE OF A MODERN CITY - Baibak, Diana; Dreval, Iryna (Theory and practice of design, 2024)
This research is aimed at the spatial provision of a healthy lifestyle for citizens, which is one of the important tasks of today according to the concept of sustainable development and relevant government guidelines. As a part of effective architectural and urban planning measures, the work identifies the creation of functional and aesthetic conditions for the implementation of physical activity among the population, specifically sports and leisure. The research has justified the relevance of forming open sports and recreational facilities, sports and leisure complexes (SLC), which create spatial conditions not only for physical activity but also for enhancing social interaction among the population. It is emphasized that significant attention is currently given to the development and design of the environment of these objects in Ukraine, positively impacting the aesthetic qualities of urban districts. The research problem lies in the insufficient study of the characteristics of urban planning organization of these objects within the structure of established urban spaces. The analysis of scientific works on this issue has proved the expediency of deepening the knowledge in the specified aspect. Purpose. This work aimed to determine the features of forming sports and leisure complexes within the structure of residential areas, depending on the nature of residential buildings that have evolved during different historical periods. Methodology. In this study, various methods were employed, including data synthesis from scientific sources and regulatory frameworks; empirical research methods (observation, measurement, comparison) during the on-site examination of urban spaces; iconographic analysis when investigating project-practical experience in forming the SLC; cartographic analysis in studying the planning features of residential development across different historical periods; logical and graphical modeling. The investigation of residential development was conducted in Kharkiv city. Results. Three main types of SLCs have been identified based on their size and equipment characteristics. Using the example of the city of Kharkiv, the possibilities of placing the researched facilities within the structure of residential development are examined across three periods: the 1930’s–1940’s, the 1950’s–1970’s, and the 1980’s–1990’s. These periods differ in morphological characteristics and spatial resources for the formation of various types of modern sports and leisure complexes. Scientific novelty. Conclusions have been drawn regarding the feasibility of the formation of first and second types of SLCs in shared areas within courtyard spaces of mass residential developments, as well as the implementation of second and third types of SLCs within the structure of landscaped open public spaces (mainly parks) or on vacant spaces. Practical relevance. This work will be useful as an effective tool for developing projects aimed at shaping the sports and leisure environments of cities, as well as serving as an informational resource for investors.